Preoperative Warfarin Reversal for Early Hip Fracture Surgery. (April 2015) - Moores, Thomas Steven; Beaven, Alastair; Cattell, Andrew Edwin; Baker, Charles; Roberts, Philip John
Purpose: To evaluate our hospital protocol of low-dose vitamin K titration for preoperative warfarin reversal for early hip fracture surgery. Methods: Records of 16 men and 33 women aged 63 to 93 (mean, 81) years who were taking warfarin for atrial fibrillation (n=40), venous thromboembolism (n=9), cerebrovascular accident (n=3), and prosthetic heart valve (n=3) and underwent surgery for hip fractures were reviewed. The 3 patients with a prosthetic heart valve were deemed high risk for thromboembolism and the remainder low-risk. The international normalised ratio (INR) of patients was checked on admission and 6 hours after administration of vitamin K; an INR of <1.7 was considered safe for surgery. Results: No patient developed venous thromboembolism within one year. The 30-day and one-year mortality was 8.2% and 32.6%, respectively. For the 46 low-risk patients, the mean INR on admission was 2.6 (range, 1.1–4.6) and decreased to <1.7 after a mean of 2.2 (range, 0–4) administrations of 2 mg of vitamin K. Their INR was <1.7 within 18 hours (mean, 14 hours). 78% of patients underwent surgery within 36 hours. In the 22% of patients who did not undergo surgery within 36 hours, the delay was due to insufficient operative time or the patient being medically unfit for surgery. The 3 high-risk patients underwent bridging therapy of low-molecular-weight heparin and received no vitamin K; their mean INR on admission was 3.2 (range, 3.1–3.3) and the mean time to surgery was 5.3 (range, 3–8) days. Two low-risk patients and one high-risk patient died within 5 days of surgery. Conclusion: The low-dose intravenous vitamin K protocol is safe and effective in reversing warfarin within 18 hours. Hip fracture surgery within 36 to 48 hours of admission improves morbidity and mortality.